2017
DOI: 10.1111/ijpp.12423
|View full text |Cite
|
Sign up to set email alerts
|

Hospital pharmacists’ and patients’ views about what constitutes effective communication between pharmacists and patients

Abstract: Pharmacists and patients provided valuable insights about what makes pharmacist-patient interactions effective. Patient-identified preferences for pharmacist-patient exchanges may help guide pharmacy students and practitioners to engage patients in effective conversations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This is not surprising as CAT suggests that speakers’ goals for their conversation will influence their communication behaviours (Gasiorek & Giles, 2012). In addition, as we have previously found, pharmacists and patients may have multiple goals (Chevalier et al, 2017a). This concept is consistent with the multiple goal theory research (Wilson, 2019) and congruent with the influence of different identities assumed (e.g., social, professional) as per CAT (Giles, 2008a).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is not surprising as CAT suggests that speakers’ goals for their conversation will influence their communication behaviours (Gasiorek & Giles, 2012). In addition, as we have previously found, pharmacists and patients may have multiple goals (Chevalier et al, 2017a). This concept is consistent with the multiple goal theory research (Wilson, 2019) and congruent with the influence of different identities assumed (e.g., social, professional) as per CAT (Giles, 2008a).…”
Section: Discussionmentioning
confidence: 86%
“…Patients stressed the importance of well-explained information, how to obtain their medications, and pharmacists’ interpersonal skills. Pharmacists felt patients were confident in self-managing their medications when patients indicated they were engaged in the conversation by asking relevant questions and using appropriate non-verbal communication such as nods and eye contact (Chevalier et al, 2017a).…”
Section: Using Communication Accommodation Theory To Interpret Pharmamentioning
confidence: 99%
“…Shortages of CPs prevent proper collaboration such that understaffed pharmacists were overloaded with responsibilities, thus affecting the quality of CPS. 42 Previous studies have found that the initiation of CPS by healthcare bodies or government was a facilitator to implementation. 27 However, we did not find any governmental or institutional policies in place to provide funding to advocate the implementation of paediatric CPS within the included studies.…”
Section: Penetrationmentioning
confidence: 99%
“…CAT proposes that individuals are motivated to be accommodative or nonaccommodative with their speech partners. The usefulness of CAT as a model to explain the dynamics in different hospital settings is well-documented in the literature (e.g., Chevalier et al, 2017; Gallois et al, 2015; Watson et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%